Peran Guru Penggerak Dalam Meningkatkan Karakter Peserta Didik Melalui Penerapan Budaya Positif Pada Pembelajaran PAI Dan Budi Pekerti - yamlean, sumira (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2025)
The character building of the nation's children must make various efforts in order to continue to make students have good character, the driving teacher who has studied the positive culture module during his education is expected to be able to implement the module in his role. This study aims to determine the role of motivating teachers in improving the character of students in the application of positive culture in PAI and ethics subjects at SMP Negeri 7 Tual and SMP Negeri 11 Tual; and to determine the inhibiting factors in the application of positive culture material to improve the character of students in PAI and ethics subjects at SMP Negeri 7 and SMP Negeri 11 Tual. Descriptive-qualitative type of research, the research subjects are principals, driving teachers and students. Data collection techniques using observation, interviews and documentation. Research results: 1) The role of the driving teacher as a driver of change in the form of realizing learning that favors students, collaboration with fellow teachers in habituation, real action and harvesting learning outcomes, opening discussion space and involving students in learning and using varied learning media. While the role of the driving teacher as a role model in the form of encouraging achievement improvement, encouraging, inspiring, respecting diversity, community mobilizers, and 2) The inhibiting factors are the low level of concern and understanding of parents, the attendance of students is not maximized, the enthusiasm for learning of students is still low, the commitment of all school residents is still low, the lack of discipline and the incomplete understanding of students towards positive culture.